Potato soup: analysis of cultivated potato gene bank populations reveals high diversity and little structure - Tuttle, Heather K.; Del Rio, Alfonso H.; Bamberg, John B.; Shannon, Laura M. (Frontiers in Plant Science, 2024)
Cultivated potatoes are incredibly diverse, ranging from diploid to pentaploid and encompass four different species. They are adapted to disparate environments and conditions and carry unique alleles for resistance to pests and pathogens. Describing how diversity is partitioned within and among these populations is essential to understanding the potato genome and effectively utilizing landraces in breeding. This task is complicated by the difficulty of making comparisons across cytotypes and extensive admixture within section petota. We genotyped 730 accessions from the US Potato genebank including wild diploids and cultivated diploids and tetraploids using Genotype-bysequencing. This data set allowed us to interrogate population structure and diversity as well as generate core subsets which will support breeders in efficiently screening genebank material for biotic and abiotic stress resistance alleles. We found that even controlling for ploidy, tetraploid material exhibited higher observed and expected heterozygosity than diploid accessions. In particular group chilotanum material was the most heterozygous and the only taxa not to exhibit any inbreeding. This may in part be because group chilotanum has a history of introgression not just from wild species, but landraces as well. All group chilotanum, exhibits introgression from group andigenum except clones from Southern South America near its origin, where the two groups are not highly differentiated. Moving north, we do not observe evidence for the same level of admixture back into group andigenum. This suggests that extensive history of admixture is a particular characteristic of chilotanum.Deleted: We genotyped a subset of the US potato genebank 138 collection in Sturgeon Bay, Wisconsin,